Why Fiscal Dynamics Occur in Samarinda City ? - Adi Wijaya; Juliansyah Roy; Dio Caisar Darma (Jurnal Ekonomi dan Studi Pembangunan, 2019)
The aim to be achieved in the study is to analyze and identify the degree of fiscal decentralization in the City of Samarinda during 2014-2018. This type of research is quantitative and the data source used is secondary data. The data is based on time series during budget year of 2014-2018, which was compiled through the publication of the Regional Revenue Agency and Central Bureau of Statistics Samarinda City. The analytical tool used is Degree of Fiscal Decentralization.Simple conclusions that can be obtained based on the analytical tool, namely: (1) The average ratio of Regional Original Income to Regional Revenues is 3,44% (very less); (2) The average ratio of Tax Sharing and Non Tax/Natural Resources Sharing to Regional Revenues is 39,69% (sufficient); (3) The average ratio of Balanced Budget to Regional Revenues is 64,51% (very good); (4) The average ratio of Regional Original Income to Regional Expenditures is 11,94% (less); (5) The average ratio of Regional Original Income to Capital Expenditures is 42,75% (good); and (6) The average ratio of Tax Sharing, Non Tax/Natural Resources Sharing, and Regional Original Income to Regional Expenditure is 47,20% (good).